Immunological studies in angioimmunoblastic lymphadenopathy. - Skibin, A (1980)
Immunological studies were carried out on two female patients with angioimmunoblastic lymphadenopathy (AIL). Both presented with fever, lymphadenopathy, hepatosplenomegaly, rash and apparent ampicillin hypersensitivity. During the active phase of the disease, cellular immunity was depressed and T cell blastogenesis induced by lectins was abnormal. In the first patient, a non-dialysable plasma factor was found that inhibited normal lymphocyte blastogenesis, the removal of which enhanced the activation of AIL lymphocytes. This inhibitory plasma factor was also observed in the second patient during relapse of the disease. The latter patient responded well to steroid and levamisole therapy, showing clinical remission and a return of in vivo and in vitro parameters of cellular immunity. Defective B cell regulation due to impaired suppressor function, followed by immunoglobulin overproduction, is suggested to occur in AIL.